Stres Akademik dan Mekanisme Koping Mahasiswa pada Masa Pandemi Covid-19 - Sita Irnadianis Irfada; Keksi Girindra Swasti; Reza Fajar Amalia (Journal of Bionursing, 2023)
Background: The Covid-19 pandemic has an impact on learning patterns so that it requires students to adapt to this situation. The stressor is felt more by first year students because they have to make adjustments to a different academic environment while in high school. Objective: The aim of the research is to describe the academic stress and coping mechanisms of health fakulty students. Method:This study uses a quantitative descriptive research design. The research population was health fakulty Unsoed students. Samples were selected using Stratified Random Sampling techniqueand obtained respondents a number of 269 respondents. This research uses academic stress inventory questionnaire and stress coping style inventory. Data analysis was performed univariately. Result: Characteristics of the majority of respondents were women (77.3%), aged 18 years and came from the nursing department (24.5%). The highest frequency of academic stress experienced by students is teachers stress (188), results stress (210), tests stress (218), studying in group stress (167), peer stress (126), time management stress (126), self - inflicte stress (154). As for the application of coping mechanisms, the majority of respondents applied active emotional coping, 177 respondents (65.8%). The highest score on the academic stress questionnaire is found in the 15th item, namely 125 (46.5%) respondents. Conclusion: The majority of students apply active emotional coping in dealing with academic stress. It is better if the application of coping mechanisms to students is not only aimed at calming down, but also being able to solve existing problems